Current issues on journalism ethics - Frost, Chris (Henry Stewart Talks, 2010)
Contemporary journalism ethics, Issues that are particularly significant for changes in media practice happening with the development of computer technology, Privacy and its impact on journalism in the UK since the introduction of the Human Rights Act
Archived at 2022/04/12